2019
DOI: 10.1038/s41598-019-42269-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nano Crystal Size on the X-ray Diffraction Patterns of Biogenic Hydroxyapatite from Human, Bovine, and Porcine Bones

Abstract: This paper focuses on the study of the effect of the change of the crystal size on the shape and width of the X-ray diffraction patterns for defatted and deproteinized bones as well as incinerated biogenic hydroxyapatite obtained from bovine, porcine, and human bones. Inductively Couple Plasma showed the presence of some ions such as Mg, K, Al, Fe, Zn, and Na for all samples. The nanometric size of the crystals was determined through High Resolution Transmission Electron Microscopy in which ordered crystals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(125 citation statements)
references
References 37 publications
2
101
1
1
Order By: Relevance
“…Nowadays, there is increasing interest in different fields of nanomaterials such as tissue engineering. One of these is the hydroxyapatite from biological sources such as bovine due to their different applications [ 4 ]. In this case, hydroxyapatite obtained from cow, pig, and chicken bones was selected.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is increasing interest in different fields of nanomaterials such as tissue engineering. One of these is the hydroxyapatite from biological sources such as bovine due to their different applications [ 4 ]. In this case, hydroxyapatite obtained from cow, pig, and chicken bones was selected.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 According to recent research results, the size of the HAp crystal is reported to be 21 ± 9 nm in length and 6 ± 1.5 nm in width. 7 Moreover, the c -axis of HAp plates were often aligned parallel to the longitudinal direction of collagen fibrils. 8 Many studies on bone tissue growth and regeneration are ongoing, and from a materials science point of view, the HAp crystal growth process occurs in the body in a specific morphology with micro/nanometer and atomic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray diffraction patterns were obtained by using a Rigaku Ultima IV diffractometer (Tokyo, Japan) according to the method as reported by Hernández-Becerra et al (2020) [ 17 ]. The crystallite size (CS) was obtained with the Scherrer’s equation (Equation (1)) [ 21 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the absolute degree of crystallinity (ADC) was obtained from X-ray diffraction data by measuring the ratio of the crystalline area and the total area in the diffractogram [ 21 ] (Equation (2)). …”
Section: Methodsmentioning
confidence: 99%